Intimate partner violence against ever-partnered women in Europe: Prevalence and associated factors—Results from the violence against women EU-wide survey - Barbier, Alice; Chariot, Patrick; Lefèvre, Thomas (Frontiers in Public Health, 2022)
Study questions To describe the prevalence of physical, sexual, and psychological intimate partner violence (IPV) against women in the European Union (EU) and to search for their determinants among demographic, socioeconomic, health-related factors, and partner characteristics. Methods Observational study. Data from the violence against women survey, the first study conducted in the EU, which simultaneously measured all dimensions of IPV and many characteristics. The EU Agency for Fundamental Rights randomly conducted face-to-face interviews among the 28 countries with 42,002 women aged 18–74 who resided in the survey country and spoke the language. IPV is defined by a positive answer to at least one question about physical, sexual, or psychological violence perpetrated by a current or ex-partner. Findings Among the 40,357 women having already been in a relationship, 51.7% (51.2–52.2) reported having been victims of violence in their lifetime. The prevalence of physical, sexual, and psychological IPV was, respectively, 20.0% (19.6–20.4), 8.4% (8.2–8.7), and 48.5% (48.1–49.0). Women, who were younger, employed, had highly qualified work, had at least one immigrant parent, lived in an urban setting, were unmarried, separated, divorced, widowed, childless, cohabited with a partner, and others over the age of 18, had worse self-perceived health, or a history of violence before the age of 15 were more likely to report IPV. It was the same when their partners had a lower level of education, no work, were home staying, earned less than they did, were involved in 10 years of relationship, were frequently drunk, or were violent otherwise. Major implication The lifetime prevalence of reported IPV among women in Europe is high and likely underestimated. The results emphasize the importance of a comprehensive definition of IPV and partners' characteristics. They highlight socioeconomic differences and poorer health status for victims of IPV.